Amin Abdullah dan Paradigma Integrasi Interkoneksi - Masyitoh, Dewi; Mustika, Rahma Dewi; Alfaza, Ahilla Salma; Hidayatullah, A F; A Hasyim, Umar Al Faruq (CV. Creative Tugu Pena, 2020)
The aim of this research analysed the understanding of concept Amin Abdullah thoughts and the integration-interconnection paradigm. The method was library research who taken from many literary from journals and books. Analysing data used content analysis and descriptive analysis. The result show that the concept of Amin Abdullah was influenced by Abid Al Jabiri who sparked Trilogi Epistimologi: Epistimologi Bayani, Episimology Irfani, and Epistimologi Burhani.Al Jibri was famous philosopher. Keywords: Amin Abdullah Thought, Integration-Interconnection Paradigm